(untitled) - Rekdal, Paisley (America, 2007)
The Invention of the Kaleidoscope is a book of poetic elegies that discuss failures: failures of love, both sexual and spiritual; failures of the body; failures of science, art and technology; failures of nature, imagination, memory and, most importantly, the failures inherent to elegiac narratives and our formal attempt to memoralize the lost. But the book also explores the necessity of such narratives, as well as the creative possibilities implicit within the “failed elegy,” all while examining the various ways that self-destruction can turn into self-preservation.
Keywords: American poetry,Thơ Mỹ